Identification of zebrafish steroid sulfatase and comparative analysis of the enzymatic properties with human steroid sulfatase. Issue 185 (January 2019) - Kurogi, Katsuhisa; Yoshihama, Maki; Williams, Frederick E.; Kenmochi, Naoya; Sakakibara, Yoichi; Suiko, Masahito; Liu, Ming-Cheh
Graphical abstract: Highlights: Zebrafish steroid sulfatase (zfSts) was identified in this study. zfSts was capable of hydrolyzing steroid sulfate including estrone-sulfate. Catalytic properties of zfSts were comparable to those of human STS. Abstract: Steroid sulfatase (STS) plays an important role in the regulation of steroid hormones. Metabolism of steroid hormones in zebrafish has been investigated, but the action of steroid sulfatase remains unknown. In this study, a zebrafish sts was cloned, expressed, purified, and characterized in comparison with the orthologous human enzyme. Enzymatic assays demonstrated that similar to human STS, zebrafish Sts was most active in catalyzing the hydrolysis of estrone-sulfate and estradiol-sulfate, among five steroid sulfates tested as substrates. Kinetic analyses revealed that the K m values of zebrafish Sts and human STS differed with respective substrates, but the catalytic efficiency as reflected by the V max / K m appeared comparable, except for DHEA-sulfate with which zebrafish Sts appeared less efficient. While zebrafish Sts was catalytically active at 28 °C, the enzyme appeared more active at 37 °C and with similar K m values to those determined at 28 °C. Assays performed in the presence of different divalent cations showed that the activities of both zebrafish and human STSs were stimulated by Ca 2+, Mg 2+, and Mn 2+, and inhibited by Zn +2 and Fe 2+ . EMATE and STX64, two known mammalian steroid sulafatase inhibitors, were shown to be capable of inhibiting the activity of zebrafish Sts. Collectively, the results obtained indicated that zebrafish Sts exhibited enzymatic characteristics comparable to the human STS, suggesting that the physiological function of STS may be conserved between zebrafish and humans.